Question

( begin{aligned} L H S=1+4 operatorname{cosec}^{2} theta cot ^{2} theta & =&left(cos alpha^{2} theta-cot ^{2} thetaright)^{2}+4 cos u^{2} theta cot ^{2} theta =& operatorname{cosec}^{4} theta+cot ^{4} theta-2 operatorname{cosec}^{2} theta cot ^{2} theta+4 operatorname{cosec}^{2} theta cot ^{2} theta =& operatorname{cosec}^{4} theta+cot ^{4} theta+2 operatorname{cosec}^{2} theta cot ^{2} theta =&left(operatorname{cosec}^{2} theta+cot ^{2} thetaright)^{2} =& R H S text { Lence, proved. } end{aligned} )

# 1+ 4cosec20 cot? 0 = (cosec2 + cot20)

Solution